Merrill chemistry : - Smoot, Robert C. (Glancoe, 1993)
Confusing explainations, and poor overall graphics and coloring. Not straight-forward enough. The beginning chemistry student may find it hard to understand. Gives too many extraneous details that do not help the reader understand the necessary concepts of basic chemistry.